COVID-19's Impact on the Economy - Patil, Maharshi J (Journal of Advanced Research in Service Management, 2022)
At present time world is facing from the coronavirus disease mentioned as COVID-19. The first case of the coronavirus was reported within the December, 2019 within the Wuhan city of China which is known because the main transportation hub of China. After the spread of COVID-19 many countries have close up their sea ports and airports. They banned the import and export activities. Also, China is that the main distributor of the raw materials which affect the manufacturing activities across the planet because of lockdowns. India is that the developing country because of the COVID-19 spread the cases reported within India government has lockdown the country for 41 days which affected the manufacturing activities and majorly it affects the supply chains and economy of the country. Within this paper we’ve discussed the effect of COVID-19 on Indian economy and on supply chains in India. There are total of 18 critical barriers are acknowledged which affected the supply chains within India. It’s expected that this study will helpful the researchers to develop the conceptual models to beat from this issue.